2023
DOI: 10.1186/s13024-022-00593-1
|View full text |Cite
|
Sign up to set email alerts
|

Advances in sequencing technologies for amyotrophic lateral sclerosis research

Abstract: Amyotrophic lateral sclerosis (ALS) is caused by upper and lower motor neuron loss and has a fairly rapid disease progression, leading to fatality in an average of 2-5 years after symptom onset. Numerous genes have been implicated in this disease; however, many cases remain unexplained. Several technologies are being used to identify regions of interest and investigate candidate genes. Initial approaches to detect ALS genes include, among others, linkage analysis, Sanger sequencing, and genome-wide association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 225 publications
1
6
0
Order By: Relevance
“…More recently, the discovery of genes associated with ASL has been shifted to next-generation sequencing, such as whole-genome sequencing (WGS) and RNA-Seq. Many WGS studies have confirmed previous findings and identified many common and rare variants associated with ASL 15,16 .…”
Section: Yangsupporting
confidence: 60%
See 2 more Smart Citations
“…More recently, the discovery of genes associated with ASL has been shifted to next-generation sequencing, such as whole-genome sequencing (WGS) and RNA-Seq. Many WGS studies have confirmed previous findings and identified many common and rare variants associated with ASL 15,16 .…”
Section: Yangsupporting
confidence: 60%
“…More recently, the discovery of genes associated with ASL has been shifted to next-generation sequencing, such as whole-genome sequencing (WGS) and RNA-Seq. Many WGS studies have confirmed previous findings and identified many common and rare variants associated with ASL 15, 16 . Brown et al have performed RNA-Seq analysis on the ASL postmortem cortex samples of NYGC ALS Consortium and found that TDP-43 loss resulted from retrotransposon and ALS-risk SNPs drive mis-splicing and depletion of UNC13A 17, 18 .…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, efforts to include unique molecular identifiers within the Iso-Seq protocol have been described [ 54 ]. With improvements such as depletion-based strategies of unwanted overexpressed transcripts, [ 55 ] concatenation workflows like PB_FLIC-Seq, and sequencing platform upgrades such as the Revio that offer larger SMRT Cell capacity, [ 56 ] Iso-Seq provides a new area of investigation focusing on alternative splicing and isoform differences in comparator and disease tissues that may control phenotypic presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the integration of phi29 DNA polymerase has played a role in slowing DNA translocation and further reducing the error rate in ONT [ 15 ]. Although these accuracies still fall slightly short compared to SRS, PacBio's latest LRS technology iteration, Revio, has reached an impressive accuracy level of 99.9%, placing it on par with SRS [ 16 ].…”
Section: Long-read Sequencing (Lrs)mentioning
confidence: 99%